Unorthodox jukebox - Mars, Bruno (New York, NY Atlantic, 2012)
"Parental advisory: explicit content"--Container insert.
Young girls -- Locked out of Heaven -- Gorilla -- Treasure -- Moonshine -- When I was your man -- Natalie -- Show me -- Money make her smile -- If I knew.
Compact disc.
Bruno Mars, vocals and instruments; with accompanying musicians.
Keywords: Rhythm and blues music; Rap (Music); Popular music -- 2011-2020.